2021
DOI: 10.7759/cureus.12750
|View full text |Cite
|
Sign up to set email alerts
|

Jarisch-Herxheimer Reaction After Cephalosporin Administration in Syphilis

Abstract: The Jarisch-Herxheimer reaction (JHR) is a well-described entity most commonly occurring after the treatment of syphilis with penicillin. Patients often experience flu-like symptoms, in addition to worsening of cutaneous manifestations of syphilis. Severe reactions are uncommon but may include signs of exaggerated systemic inflammatory response. We report a case of a 33-year-old male with secondary syphilis who was treated with ceftriaxone and subsequently developed fluid-refractory hypotension requiring vasop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…He also tolerated the further administration of ceftriaxone. 7 The other case about JHR in secondary syphilis with eosinophilia by Elias et al reported facial erythema and edema after penicillin administration which was treated with prednisone. 8 In our case, co-trimoxazole administration was stopped and we did not re-challenge co-trimoxazole as the antibiotics were changed to meropenem and tigecycline.…”
Section: Discussionmentioning
confidence: 99%
“…He also tolerated the further administration of ceftriaxone. 7 The other case about JHR in secondary syphilis with eosinophilia by Elias et al reported facial erythema and edema after penicillin administration which was treated with prednisone. 8 In our case, co-trimoxazole administration was stopped and we did not re-challenge co-trimoxazole as the antibiotics were changed to meropenem and tigecycline.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ceftriaxone was preferred due to its lower risk of Jarisch-Herxheimer reactions and other complications. There have been isolated cases reported where ceftriaxone has caused Jarisch-Herxheimer reactions, 22 but according to literature data, cross-allergic reactions to ceftriaxone have been observed very rarely. 14 In our clinics, the use of ceftriaxone in pregnant women diagnosed with syphilis as an alternative option has been implemented since 2004.…”
Section: Discussionmentioning
confidence: 99%